Anidación de la tortuga blanca, Chelonia mydas (Linnaeus, 1758) (Testudines: Cheloniidae), en Isla Contoy, México. - Durán Nájera, Juan José (Revista de Biología Tropical, 1991)
Oreen turtles (Chelonia mydas) nested in Contoy Island from August through October in 1984 and from Iune through September in 1985, tbe second seems to be regular season. 1 recorded 44 specimens in both seasons, tbe smallest female measured 87 cm, and the largest 117 cm of straight carapace lengt. Nests located nearer than 6 m from high tide line must be located in order to hatch. The mean numbers of eggs per nest for 1984 and 1985 were 98 and 114, respectively. Incubation in situ took around 50 days. In the 1985 nesting season, each C. mydas female nested a mean of 1.6 times, with a mean nesting interval of 22 days.